Identification of non-sharia compliant activity in conventional insurance - SHOFAWATI, A (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Insurance is a commercial institution that has the function of protecting individuals, organizations and companies against risk. This document is intended to identify non-shariah activities in specific insurance. One of the disadvantages of conventional insurance is the existence of an activity that does not comply with sharia such as Reba, Maysir and Gharar. Islamic insurance has some solutions to minimize activity that does not comply with the sharia of conventional insurance.